Genome-Wide Association Study of Meat Quality Traits in Nellore Cattle - Magalhã, Ana F. B.; De Camargo, Gregório M. F.; Junior Fernandes, Gerardo A.; Gordo, Daniel G. M.; Tonussi, Rafael L.; Costa, Raphael B.; Espigolan, Rafael; De Silva, Rafael M.O.; Bresolin, Tiago; De Andrade, Willian B.F.; Takada, Luciana; Feitosa, Fabieli L. B.; et al. (Public Library of Science (PLoS), 2016)
The objective of this study was to identify genomic regions that are associated with meat quality traits in the Nellore breed. Nellore steers were finished in feedlots and slaughtered at a commercial slaughterhouse. This analysis included 1,822 phenotypic records of tenderness and 1,873 marbling records. After quality control, 1,630 animals genotyped for tenderness, 1,633 animals genotyped for marbling, and 369,722 SNPs remained. The results are reported as the proportion of variance explained by windows of 150 adjacent SNPs. Only windows with largest effects were considered. The genomic regions were located on chromosomes 5, 15, 16 and 25 for marbling and on chromosomes 5, 7, 10, 14 and 21 for tenderness. These windows explained 3,89% and 3,80% of the additive genetic variance for marbling and tenderness, respectively. The genes associated with the traits are related to growth, muscle development and lipid metabolism. The study of these genes in Nellore cattle is the first step in the identification of causal mutations that will contribute to the genetic evaluation of the breed.